Moving into the digital era: a novel experience with the first full-field digital mammography system in Malaysia - Ranganathan, S.; Faridah, Y.; Ng, K.H. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2007)
FFDM does improve quality of mammography service by providing better workflow time and archiving system, with good diagnostic accuracy.